2022
DOI: 10.1093/jtm/taac085
|View full text |Cite
|
Sign up to set email alerts
|

Monkeypox virus containment: the application of ring vaccination and possible challenges

Abstract: Due to the pandemic potential of monkeypox, the application of ring vaccination would be of great value in breaking the chain of transmission as well as in preventing the occurrence of severe disease. Accompanying challenges should be overcome to properly contain the disease before it is declared pandemic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 2 publications
0
25
0
Order By: Relevance
“…Public health measures to prevent forward transmission of MPXV focus on spreading knowledge and awareness especially among most-at-risk groups; however, the central preventive measure relies on vaccination [ 17 , 29 , 30 ]. It has been previously shown that smallpox vaccination provides at least 85% effectiveness to prevent HMPX; therefore, vaccination of most-at-risk groups has already been considered [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Public health measures to prevent forward transmission of MPXV focus on spreading knowledge and awareness especially among most-at-risk groups; however, the central preventive measure relies on vaccination [ 17 , 29 , 30 ]. It has been previously shown that smallpox vaccination provides at least 85% effectiveness to prevent HMPX; therefore, vaccination of most-at-risk groups has already been considered [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Primary prevention with vaccination can be critical for control of MPX [ 4 ]. The benefits of ring vaccination are double-fold: it can break the chain of virus transmission and, bring to a halt the course of a severe disease [ 5 ].…”
mentioning
confidence: 99%
“…Specific to the MPX outbreak and due to the nature of the disease where there is a slow transmission and a long incubation period, ring vaccination offers a promising solution [ 5 ]. Furthermore, ease of implementation, efficient use of available resources (limited vaccines and staff), lower odds of spreading, limited number of vaccines required to complete the ring, and greater efficacy for isolated communities with smaller population sizes are all advantageous to health authorities ( Fig.…”
mentioning
confidence: 99%
“…In order to control the situation, 200 of the total one thousand doses of rVSV-ZEBOV Ebola vaccines available in the country are expected to be sent to Beni this week. “Ring-vaccination”- a strategy where the first and second level contacts of the confirmed cases are vaccinated to curb the spread of the virus was launched on 25 th Aug 2022 [ 12 ]. Ring vaccination is one of the pivotal strategies to put a halt to the transmission and to control the spread of the disease [ 12 ].…”
mentioning
confidence: 99%
“…“Ring-vaccination”- a strategy where the first and second level contacts of the confirmed cases are vaccinated to curb the spread of the virus was launched on 25 th Aug 2022 [ 12 ]. Ring vaccination is one of the pivotal strategies to put a halt to the transmission and to control the spread of the disease [ 12 ].…”
mentioning
confidence: 99%